Plant Bioresources and Diversity of Home Gardens in Thanga Village, Manipur: Landscape Connected to Loktak Lake, a Ramsar Site - Langlentombi, L. Chanu; Ningombam, Arati; Basudha, Ch.; Ameeta, A.; Singh, T. Basanta; Singh, Kh. Rishikanta; Meitei, W. Anand; Premabati, Ch.; Tania, Chongtham; Anal, Bs. Hmannihring (International Journal of Bio-resource and Stress Management, 2025)
A study was conducted during August–November, 2024 at Thanga village in Bishnupur district of Manipur, India to study the plant bioresources and species diversity of home gardens in Thanga village which is a community closely tied to Loktak Lake’s ecological and cultural landscape. Home gardens play a very significant role in reservoirs of plant diversity and have been contributing immensely to biodiversity conservation, food security, and preservation of traditional knowledge. Given the rising vulnerability of forests to climate change and human disturbances, home gardens can be seen as a sustainable alternative for conserving plant diversity while supporting local livelihoods. A total of 70 plant species and 38 families were documented, with Zingiberaceae being the most dominant. The species were categorized into edible, medicinal, ornamental, fuelwood and construction uses. Species richness ranged from 8.71 to 12.56, with edible plants dominating. Diversity indices, such as Shannon-Wiener index and Simpson’s diversity index, indicated considerable biodiversity and evenness, and hence, the necessity of home gardens in maintaining ecological stability, ensuring food security, and preserving traditional knowledge. The study further emphasizes the home garden composition in relation to the surrounding environment, especially the impact of Loktak Lake. Loktak Lake provides much-needed ecological support, which influences plant growth and species selection in home gardens. The reliance of the villagers on these gardens for subsistence and livelihood security indicates the cultural and economic importance of home garden bioresources. It brought forward the imperative necessity of maintaining sustainable management practices to preserve biodiversity while challenging emerging changes.